(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the concept of tutoring in foreign studies, its essence and content, as well as tutor activity in the practice of the International Institute of Management “LINK”, tutor functions in the system of open distance professional education (ODPO), the role of the tutor in implementation of the educational trajectory.